2020
DOI: 10.1108/jbim-02-2020-0098
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in veterinary markets: opinion leaders’ social capital

Abstract: Purpose This study aims to identify how the personal social capital of opinion leaders contributes to the market adoption of start-up innovations. Design/methodology/approach A design-oriented case study is undertaken with a start-up company focusing on the development and commercialization of innovations in the veterinary market. Based on a literature review, the authors examine the social capital in value creation and the role of opinion leaders and use qualitative methodology and semi-structured in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Second, this study addresses the importance of relational and bricolage capabilities in a resource-constrained context and provides an insight into how exporting firms can leverage their capabilities to overcome resource-based constraints and improve their innovation in international markets. In today’s competitive business environments, innovation is regarded as a valuable tool for improving competitiveness (Zhang et al , 2015; Chowdhury et al , 2017; Kulangara et al , 2016; Leyer et al , 2017; Vos et al , 2018; Anning-Dorson, 2018; Golini and Gualandris, 2018; Kwak et al , 2018; Kulkov et al , 2021). Developing economies encounter more barriers to innovation because of deficiencies in terms of their education system, the institutional environment and financial resources (Bradley et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study addresses the importance of relational and bricolage capabilities in a resource-constrained context and provides an insight into how exporting firms can leverage their capabilities to overcome resource-based constraints and improve their innovation in international markets. In today’s competitive business environments, innovation is regarded as a valuable tool for improving competitiveness (Zhang et al , 2015; Chowdhury et al , 2017; Kulangara et al , 2016; Leyer et al , 2017; Vos et al , 2018; Anning-Dorson, 2018; Golini and Gualandris, 2018; Kwak et al , 2018; Kulkov et al , 2021). Developing economies encounter more barriers to innovation because of deficiencies in terms of their education system, the institutional environment and financial resources (Bradley et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The opinion leadership literature has shown that individual opinion leaders have acquired social capital, which allows them to achieve better outcomes (Kulkov et al. , 2021) and is considered experts in the field (Leal et al.…”
Section: Background and Hypothesismentioning
confidence: 99%
“…Employee-generated content. The opinion leadership literature has shown that individual opinion leaders have acquired social capital, which allows them to achieve better outcomes (Kulkov et al, 2021) and is considered experts in the field (Leal et al, 2014). Professional networking platforms enable users to register as employees of specific companies and reveal their current and past employment positions, responsibilities, and achievements.…”
Section: 33mentioning
confidence: 99%
“…This means that policymakers need to support new technologies in health-care implementation, for example, through being flexible in adjusting legislation to accommodate most promising and beneficial technologies. We expected that cooperation with universities and opinion leaders would be Implementing new technologies in healthcare important to successfully form and promote the digital solutions in focus (Kulkov et al, 2020). However, this is not entirely true for all solutions.…”
Section: Managerial and Policy Implicationsmentioning
confidence: 99%